Immune-mediated regeneration of cell-free vascular grafts in an ovine model - Bita Nasiri; Arundhati Das; Karthik Ramachandran; Sai Harsha Bhamidipati; Yulun Wu; Shriramprasad Venkatesan; Rudiyanto Gunawan; Daniel D. Swartz; Stelios T. Andreadis (npj Regenerative Medicine)
Abstract We developed acellular tissue engineered vessels (ATEV) using small intestine submucosa (SIS) incorporating heparin and a novel protein named H2R5. ATEVs were implanted into the arterial circulation of an ovine animal model, demonstrating high primary patency rates over a period of three months. Implanted grafts were infiltrated by host cells, the majority of which were monocytes/macrophages (MC/MΦ), as demonstrated by scRNA sequencing and immunostaining. They also developed functional endothelial and medial layers that deposited new extracellular matrix leading to matrix remodeling and acquisition of mechanical properties that were similar to those of native arteries. Notably, during this short implantation time, ATEVs turned into functional neo-arteries, as evidenced by the development of the vascular contractile function. Our findings underscore the potential of H2R5-functionalized ATEVs as promising candidates for tissue replacement grafts in a large pre-clinical animal model and highlight the contribution of macrophages in vascular regeneration.